De novo transcriptome assembly and analysis of differential gene expression in response to drought in European beech. - Markus Müller; Sarah Seifert; Torben Lübbe; Christoph Leuschner; Reiner Finkeldey (PLoS ONE)
Despite the ecological and economic importance of European beech (Fagus sylvatica L.) genomic resources of this species are still limited. This hampers an understanding of the molecular basis of adaptation to stress. Since beech will most likely be threatened by the consequences of climate change, an understanding of adaptive processes to climate change-related drought stress is of major importance. Here, we used RNA-seq to provide the first drought stress-related transcriptome of beech. In a drought stress trial with beech saplings, 50 samples were taken for RNA extraction at five points in time during a soil desiccation experiment. De novo transcriptome assembly and analysis of differential gene expression revealed 44,335 contigs, and 662 differentially expressed genes between the stress and normally watered control group. Gene expression was specific to the different time points, and only five genes were significantly differentially expressed between the stress and control group on all five sampling days. GO term enrichment showed that mostly genes involved in lipid- and homeostasis-related processes were upregulated, whereas genes involved in oxidative stress response were downregulated in the stressed seedlings. This study gives first insights into the genomic drought stress response of European beech, and provides new genetic resources for adaptation research in this species.